2017
DOI: 10.1111/sms.12829
|View full text |Cite
|
Sign up to set email alerts
|

Broad‐spectrum health improvements with one year of soccer training in inactive mildly hypertensive middle‐aged women

Abstract: The study tested the hypothesis that long-term soccer training has positive impact on cardiovascular profile, body composition, bone health, and physical capacity in inactive, pre-menopausal women with mild hypertension. The study applied a randomized controlled design in which physically inactive middle-aged women were separated into a soccer training group (n=19; SOC) and a control group (n=12; CON). SOC performed 128±29 (±SD) one-h small-sided soccer training sessions over one year. Blood pressure, body com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 38 publications
3
37
2
2
Order By: Relevance
“…Results of short periods of RF intervention (12 to 16 weeks) revealed that, generally, blood pressure decreases more in healthy or mild‐to‐moderate arterial hypertensive men and women when compared to a control group. Similar evidence can be found ≥1‐year interventions . These responses may be caused by a reduction in sympathetic tone and an increase in parasympathetic activity as verified by heart rate variability and heart rate measurements .…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Results of short periods of RF intervention (12 to 16 weeks) revealed that, generally, blood pressure decreases more in healthy or mild‐to‐moderate arterial hypertensive men and women when compared to a control group. Similar evidence can be found ≥1‐year interventions . These responses may be caused by a reduction in sympathetic tone and an increase in parasympathetic activity as verified by heart rate variability and heart rate measurements .…”
Section: Discussionsupporting
confidence: 75%
“…In the case of short period interventions, results seem to suggest that a short period of RF intervention can lead to meaningful decreases in blood pressure (5‐12 mm Hg) in healthy and mild‐to‐moderate hypertensive men and women . Longer interventions (one year or more) of RF training were associated with decreases of 5 mm Hg in mean arterial pressure of mild hypertensive women, while no changes were found in a control group . Furthermore, despite a decrease in the volume of training completed by healthy male participants after an initial 12‐week period, decreases in systolic and diastolic blood pressure of 8 and 3 mm Hg, respectively, were still observed .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Computation of YYIE1 test global means, SDs and quantiles (Figure 5) involved 12 studies/subgroups reporting on 770 participants (median age = 21.3 years, IQR = 18.8–44.3 years) (Metaxas et al, 2005; Castagna et al, 2006a; Lategan et al, 2011; Rowan et al, 2012; Deliceoglu, 2013; Mohr et al, 2014; Akashi et al, 2015; Fløtum et al, 2016; Julian et al, 2017; Krustrup et al, 2017; Seidelin et al, 2017). …”
Section: Resultsmentioning
confidence: 99%